Luis Alberto Mansilla, autodidacta Los caminos a la cultura de un comunista chileno (1933 - 2016) - Samaniego, Augusto (Ariadna Ediciones, 2019)
Biography of the Chilean left intellectual. Personal testimonies collected in several interviews